2020
DOI: 10.1016/j.heliyon.2020.e03870
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic beliefs among patients with schizotypal personality disorder

Abstract: This study aimed to explore the differences in pathogenic beliefs (PBs) between patients with schizotypal personality disorder (PD) and those with other PDs or without any PD. The study was conducted among 212 patients treated with psychotherapy at the Psychotherapy and Personality Disorder Clinic, Chiang Mai University between 2007 and 2019. Collected data included sociodemographic information, psychiatric disorders and personality disorder as determined by the Structured Clinical Interview for the Diagnostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
(41 reference statements)
1
2
0
Order By: Relevance
“…Notably, significant pathogenic beliefs for this personality disorder included 'others are superior or more competent than you are' and 'your feelings, needs, or behaviors are overwhelming or alienating to others.'. These findings are consistent with prior research that has identified the same significant pathogenic belief items [13] and indicate that the pathogenic beliefs in schizotypal personality disorder are not solely linked to their cognitive style. These pathogenic beliefs may contribute to stress, leading to psychiatric symptoms and motivating individuals to seek therapy.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Notably, significant pathogenic beliefs for this personality disorder included 'others are superior or more competent than you are' and 'your feelings, needs, or behaviors are overwhelming or alienating to others.'. These findings are consistent with prior research that has identified the same significant pathogenic belief items [13] and indicate that the pathogenic beliefs in schizotypal personality disorder are not solely linked to their cognitive style. These pathogenic beliefs may contribute to stress, leading to psychiatric symptoms and motivating individuals to seek therapy.…”
Section: Discussionsupporting
confidence: 90%
“…These 27 items exhibited unidimensionality and substantial reliability for both persons and items, each exceeding 0.80. The test-retest reliability over a two-week interval, calculated by intraclass correlation coefficient, was 0.65 (p < .001), indicating moderate reliability [13].…”
Section: Pathogenic Belief Scale (Pbs)mentioning
confidence: 97%
See 1 more Smart Citation
“…Pattamanusorn and colleagues hypothesized in their study that individuals with SPD experience more 'pathogenic beliefs' than those suffering from other forms of personality disorders due to the severely impaired personality functioning of SPD [10]. Pathogenic beliefs are defined as the dysfunctional and debilitating perceptions of others and oneself that disrupt normal interpersonal activities or endeavors.…”
Section: Individual and Social Impactmentioning
confidence: 99%
“…Using a retrospective cross-sectional design, the researchers examined the dissimilarities in the frequency of pathogenic beliefs among patients with SPD, other personality disorders, and those who do not suffer from any personality disorders. The participants for the study were patients diagnosed with psychiatric disorder and were receiving psychotherapy between 2007 and 2019 [10]. No confounding variables were controlled in the study.…”
Section: Individual and Social Impactmentioning
confidence: 99%